Navigational Needs and Preferences of Hospital Patients and Visitors: What Prospects for Smart Technologies? - Ženka, Jan; Macháček, Jan; Michna, Pavel; Kořízek, Pavel (International journal of environmental research and public health, 2021)
In this paper, we map navigational needs and preferences of patients and visitors to evaluate the appropriateness of a smartphone navigation application in the hospital in contrast to other, more traditional navigational cues. We test the effects of sociodemographic variables (age, gender, education) on wayfinding strategies and preferences of respondents (using chi2 tests). Empirical research is based on the survey among 928 patients/visitors of the Vítkovice Hospital in Ostrava, Czechia. We found a relatively weak association between gender and wayfinding-no major differences between men and women in navigational preferences were found. Age was the most important predictor of wayfinding. Respondents in the over-60-year age group were characteristic of a lower interest in changes of the navigational system and low willingness to use mobile applications for navigation-people between 41 years and 60 years were the biggest supporters of changes. Correspondingly, demand for improvement of navigation (including a mobile application) was positively correlated with educational level.
Keywords: Surveys and Questionnaires; age; Humans; Spatial Navigation; hospital; Female; dospělí; lidé; wayfinding; průzkumy a dotazníky; Adult; ženské pohlaví; Hospitals; Male; smartphone navigation; nemocnice; Technology; Cues; podněty; prostorová navigace; spatial abilities; mužské pohlaví; technologie; gender